(-)-Fenchone Prevents Cysteamine-Induced Duodenal Ulcers and Accelerates Healing Promoting Re-Epithelialization of Gastric Ulcers in Rats via Antioxidant and Immunomodulatory Mechanisms - Maria Elaine Cristina Araruna; Edvaldo Balbino Alves Júnior; Catarina Alves de Lima Serafim; Matheus Marley Bezerra Pessoa; Michelle Liz de Souza Pessôa; Vitória Pereira Alves; Marcelo Sobral da Silva; Marianna Vieira Sobral; Adriano Francisco Alves; Mayara Karla dos Santos Nunes; Aurigena Antunes Araújo; Leônia Maria Batista (MDPI AG, 2024)
Background: (-)-Fenchone is a naturally occurring monoterpene found in the essential oils of Foeniculum vulgare Mill., Thuja occidentalis L., and Peumus boldus Molina. Pharmacological studies have reported its antinociceptive, antimicrobial, anti-inflammatory, antidiarrheal, and antioxidant activities. Methods: The preventive antiulcer effects of (-)-Fenchone were assessed through oral pretreatment in cysteamine-induced duodenal lesion models. Gastric healing, the underlying mechanisms, and toxicity after repeated doses were evaluated using the acetic acid-induced gastric ulcer rat model with oral treatment administered for 14 days. Results: In the cysteamine-induced duodenal ulcer model, fenchone (37.5-300 mg/kg) significantly decreased the ulcer area and prevented lesion formation. In the acetic acid-induced ulcer model, fenchone (150 mg/kg) reduced (p < 0.001) ulcerative injury. These effects were associated with increased levels of reduced glutathione (GSH), superoxide dismutase (SOD), interleukin (IL)-10, and transforming growth factor-beta (TGF-β). Furthermore, treatment with (-)-Fenchone (150 mg/kg) significantly reduced (p < 0.001) malondialdehyde (MDA), myeloperoxidase (MPO), interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and nuclear transcription factor kappa B (NF-κB). A 14-day oral toxicity investigation revealed no alterations in heart, liver, spleen, or kidney weight, nor in the biochemical and hematological parameters assessed. (-)-Fenchone protected animals from body weight loss while maintaining feed and water intake. Conclusion: (-)-Fenchone exhibits low toxicity, prevents duodenal ulcers, and enhances gastric healing activities. Antioxidant and immunomodulatory properties appear to be involved in its therapeutic effects.